2018
DOI: 10.1093/jcag/gwy044
|View full text |Cite
|
Sign up to set email alerts
|

Equity and Gender Issues Among Members of the Canadian Association of Gastroenterology

Abstract: Background Gender equity has historically been a challenge within gastroenterology. Aims The Canadian Association of Gastroenterology (CAG) developed a survey to identify issues pertaining to equity and gender faced by its membership and to determine areas of action. Methods In 2014, the survey was emailed to all 1155 CAG members, and the data were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…However, research has shown that women possess equal desire to pursue surgery early on in their careers 15 . Few studies have looked at gastroenterology training from a gender perspective 16 , 17 . However, female gastroenterologists have lower engagement in leadership roles, 18 earn less money than male gastroenterologists, 19 are more likely to remain childless and receive significantly less training in endoscopy 20…”
Section: Introductionmentioning
confidence: 99%
“…However, research has shown that women possess equal desire to pursue surgery early on in their careers 15 . Few studies have looked at gastroenterology training from a gender perspective 16 , 17 . However, female gastroenterologists have lower engagement in leadership roles, 18 earn less money than male gastroenterologists, 19 are more likely to remain childless and receive significantly less training in endoscopy 20…”
Section: Introductionmentioning
confidence: 99%
“…The main conclusion was that professional success and satisfaction were attainable by female gastroenterologists, but it required greater personal sacrifice compared to males. Similar themes noted by Perera et al’s more recent survey included female gastroenterologists encountering difficulty with career advancement, achieving work-life balance and a lack of mentorship ( 10 ).…”
Section: Introductionmentioning
confidence: 68%
“…al. who had majority of respondents earning <$200,000/year ( 9 , 10 ). This could be explained by 20 years of inflation and a large proportion of non-physician respondents, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that professional success could be attained by either gender equally but it required disproportionate personal sacrifices on the part of women gastroenterologists ( 6 ). More recently, Perera et al found that female Canadian gastroenterologists continued to report more difficulty with career advancement and attaining work–life balance than their male counterparts ( 7 ).…”
Section: Introductionmentioning
confidence: 99%